Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Masyarakat di Sekitar Kawasan Hutan Kota Langsa - Muhammad Rizky; Puti Andiny; Salman Salman (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
This study aims to explain the influence of the variables, the number of family members, the number of visitors, the level of expenditure, and working hours on the income of the community around the Hutan Kota Langsa area. Data were collected through questionnaires distributed to respondents, and the sample size for this research was 52 respondents. The data analysis method employed multiple linear regression using the SPSS program. The research findings indicate that the number of family members has a positive but not significant impact on the income of the community around the Hutan Kota Langsa area. Meanwhile, the variables of the number of visitors, expenditure level, and working hours have a positive and significant impact on the income of the community around the Hutan Kota Langsa area. Simultaneously, all dependent variables have a positive and significant impact on the dependent variable, income.